PERTANGGUNGJAWABAN DIREKSI ATAS KERUGIAN PERSEROAN DALAM PERUSAHAAN GRUP - ramsay, sahur (JUSTISI, 2022)
This study aims to determine the responsibility of the board of directors for the loss of the company in the group company. In a group company, there are holding company and subsidiary companies, empirically the subsidiary is an independent legal entity, but in the economic sector it is a representation of the holding company or business support for the holding company. The non-independence of the subsidiary has implications for the responsibility of the board of directors, in the event of a loss to a third party. The research was conducted using a normative juridical/library research method, secondary data obtained, mixed, analyzed qualitatively and described descriptively. From the research, it can be concluded that if the directors of the holding company are proven legally and convincingly in running the company in bad faith or mean bad deals cause the subsidiary to suffer losses, then the directors of the holding company can be held accountable for their personal assets based on the doctrine of piercing the corporate veil and if the board of directors has more than one responsibility jointly and severally Keywords Limited Liability Companies, Directors, Group Companies